Multi-GNSS positioning - de Tarso Setti, Paulo (2020)
GNSS (Global Navigation Satellite Systems) have gained a lot of visibility in the last two decades, being currently applied in several activities that go far beyond navigation positioning, some of them requiring high precision (centimeter to millimeter), such as structural monitoring and precision agriculture. To meet these requirements, different positioning methods have been developed, such as (standard and precise) point positioning and relative positioning. More recently, the possibility real time positioning with the use of networks has emerged, both for point and relative methods. The launch of new global constellations has enabled the integration of the different systems which, when successful, offers improvements for the positioning regarding the availability of satellites, the geometry between the receiver and the satellites, ambiguity resolution and its performance when compared to the isolated use of systems. In this sense, this paper presents a review and state of the art of the main characteristics of the four global systems and the different positioning methods, highlighting the multi-GNSS integration, trends and challenges in each of them. Results comparing multi-GNSS with the four constellations positioning to GPS-only, using a 25° cutoff angle, simulating an obstructed environment, are also presented. Considering the positioning accuracy, which considers the error and standard deviation in the position estimate, the integration of the systems brought an improvement of up to 44%.